THE ROLE OF PERSONALITY CHARACTERISTICS OF ATHLETES IN COACH-ATHLETE RELATIONSHIPS - (:unkn) unknown (SAGE PUBLICATIONS INC, 2015)
This study investigated the relationship between athletes' personality characteristics and the quality of the coach-athlete relationship. 84 female (M age=20.6 yr., SD=2.8) and 129 male (M age=22.0 yr., SD=3.3) elite youth athletes competing at least for 7 yr. participated in this study. The Five-Factor Personality Inventory (short version) and the Quality of Relationships Inventory were administered to all participants. Stepwise multiple regression analysis assessed which of the five personality factors predicted scores for the different subscales of the Quality of Relationships Inventory (Depth, Support, and Conflict). Results indicated that depth of relationship was not predicted by personality factors. On the other hand, neuroticism and extraversion were significant predictors of support dimension of relationship. Analysis indicated that conscientiousness was the strongest predictor of conflict. In conclusion, athletes' personality characteristics may be important in determining the quality of the coach-athlete relationship.
Keywords: RELATIONSHIP QUALITY; PERCEPTIONS; SIMILARITY; PREDICTORS; ATTACHMENT; BEHAVIOR; SPORT; SATISFACTION; DIMENSIONS; STABILITY